2005
DOI: 10.1080/00207590444000122
|View full text |Cite
|
Sign up to set email alerts
|

Affective dimension in cognitive maps of Barcelona and São Paulo

Abstract: This paper analyses the relationship between city and affection as revealed through an investigation into the feelings and emotions of a sample of inhabitants of Barcelona and São Paulo towards their cities. A study of affection in the context of a city has its origin in the assumption that it is possible to develop an ethical‐affective rationality in the creation of spaces of both public and private interest, a dimension that can serve to optimize the action of the inhabitants of a city. The theoretical/metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Song et al [29] classified cognitive maps that reflect path topological relations but lack recognisability of district spatial elements as hybrid types. Bomfim et al [30] added individual type categories when exploring the emotional dimension of a cognitive map, which only included landmark landscapes but were more abstract and symbolic. Young [31] found that some cognitive maps basically have no spatial representation, but only consist of some landmark landscapes, such as trees and waterfalls.…”
Section: Cognitive Map Typesmentioning
confidence: 99%
“…Song et al [29] classified cognitive maps that reflect path topological relations but lack recognisability of district spatial elements as hybrid types. Bomfim et al [30] added individual type categories when exploring the emotional dimension of a cognitive map, which only included landmark landscapes but were more abstract and symbolic. Young [31] found that some cognitive maps basically have no spatial representation, but only consist of some landmark landscapes, such as trees and waterfalls.…”
Section: Cognitive Map Typesmentioning
confidence: 99%
“…Kobayashi, Preston, and Murnaghan (2011) look at how affect is produced from and through the experiences of people in place; they explore the sense of place produced by migrants from Hong Kong into Vancouver and Toronto. Bomfim and Urrutia (2005) investigate the feelings and emotions of a sample of people in Barcelona and Sao Paulo about their city. The responses, qualified by metaphor, identify dominant representations of feelings of a "city of contrast", "city of attraction", "city of destruction", "city of surprises", city of movement" and "pleasant city".…”
Section: Introductionmentioning
confidence: 99%
“…The factor of familiarity of place is closely linked to the factor of place of residence. The better the respondents know the given place, no matter whether from primary or secondary sources, the more elements they draw, and with greater accuracy [7,74,[102][103][104]. The Evans, Marrero and Butler [105] study also discovered that the number of nodes and paths increases along with familiarity of place, but the number of significant elements does not change.…”
Section: Groupmentioning
confidence: 97%